KOMPETENSI DAN LINGKUNGAN KERJA: STUDI PERILAKU KESELAMATAN PADA PELAUT - Basmala Anggun Karomah; Gartinia Nurcholis; Dessy Nur Utami (Jurnal Psikologi Poseidon, 2021)
This study aimed to determine the relationship between competence and work environment with safety behavior in seafarers at PT. ASDP Surabaya independently and simultaneously. Respondents were 41 seafarers at PT. ASDP Surabaya, taken using incidental sampling technique. The data were analyzed using multiple correlation and product moment techniques. The results of the study show that there is a relationship between competence, work environment, and safety behavior in seafarers at PT. ASDP Surabaya and the direction of the relationship is positive. The results showed that the level of safety behavior among seafarers at PT. ASDP Surabaya was in the moderate category.